2010
DOI: 10.3141/2147-09
|View full text |Cite
|
Sign up to set email alerts
|

Near Crashes as Crash Surrogate for Naturalistic Driving Studies

Abstract: Naturalistic driving is an innovative method for investigating driver behavior and traffic safety. However, as the number of crashes observed in naturalistic driving studies is typically small, crash surrogates are needed. A study evaluated the use of near crashes as a surrogate measure for assessment of the safety impact of driver behaviors and other risk factors. Two metrics, the precision and bias of risk estimation, were used to assess whether near crashes could be combined with crashes. The principles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 234 publications
(149 citation statements)
references
References 12 publications
1
126
0
1
Order By: Relevance
“…The SHRP 2 NDS results estimate the risk of talking on a handheld cell phone to be 2.2 times higher than model driving, or slightly higher than the overall distraction risk. This result seems consistent with other naturalistic and epidemiological studies when one considers the following: (i) the comparison made within the SHRP 2 NDS uses model driving, as defined previously, which is not true of crash database analyses; and (ii) a recent study (9) showed that odds ratios are somewhat underestimated when minor collisions and near-crashes are used as surrogates for crashes in the estimates obtained in previous NDSs. Because this analysis is (to our knowledge) the first of its kind to use only crashes, the determined odds ratio of 2.2 for talking on a handheld cell phone seems consistent and accurate.…”
Section: Or (95% Ci) Baseline Prevalencesupporting
confidence: 74%
See 1 more Smart Citation
“…The SHRP 2 NDS results estimate the risk of talking on a handheld cell phone to be 2.2 times higher than model driving, or slightly higher than the overall distraction risk. This result seems consistent with other naturalistic and epidemiological studies when one considers the following: (i) the comparison made within the SHRP 2 NDS uses model driving, as defined previously, which is not true of crash database analyses; and (ii) a recent study (9) showed that odds ratios are somewhat underestimated when minor collisions and near-crashes are used as surrogates for crashes in the estimates obtained in previous NDSs. Because this analysis is (to our knowledge) the first of its kind to use only crashes, the determined odds ratio of 2.2 for talking on a handheld cell phone seems consistent and accurate.…”
Section: Or (95% Ci) Baseline Prevalencesupporting
confidence: 74%
“…Near-crashes are operationally defined as having the observable factors that could lead to a crash, with one difference present: the performance of a successful evasive maneuver. Although previous studies used near-crashes as a surrogate for estimating crash risk, the accuracy and validity of combining crashes and near-crashes to estimate driver risk are just beginning to be understood (9). With the completion of the SHRP 2 NDS, however, researchers now have access to an order-of-magnitude larger sample size that allows the sole use of crash events to determine the safety outcome for risk factor evaluation.…”
mentioning
confidence: 99%
“…Second, empirical and epidemiological studies investigated crashes but omitted nearcrashes. Near-crashes share similar causal factors with crashes; therefore, both should be considered as safety critical events (Guo, Klauer, Hankey, & Dingus, 2010). Third, most driving studies on sleep disorders were limited in their participant samples, preventing investigation into any interactions between demographic factors and sleep disorders on crash risks (Barger et al, 2005;Ellen et al, 2006;Lerman et al, 1995).…”
Section: Summary Of Current Researchmentioning
confidence: 99%
“…To overcome the restriction of driving simulation and field experiment such as short test horizon and limited controlled settings [21], the 100-car Naturalistic Driving Study (NDS) was the first large-scale NDS conducted in the US [22,23], followed by the 60-Taxi NDS in Japan [24]. The UDRIVE Naturalistic Driving Study was conducted from 2012 to 2016 in seven countries in Europe [25].…”
Section: Introductionmentioning
confidence: 99%